Infectious Aneurysms Caused by Streptococcus Pyogenes in Children. Issue 10 (20th July 2022) - Higuchi, Toru; Ogawa, Eiki; Ikeyama, Takanari; Yasuda, Kazushi; Murayama, Hiroomi; Hasegawa, Tadao; Ito, Kenta
Abstract : We describe the detailed clinical course of rapidly enlarging infective aneurysms during the treatment of endocarditis and purulent pericarditis caused by Streptococcus pyogenes . We show that S. pyogenes aneurysms can enlarge rapidly within 1–2 days. Moreover, we highlight the benefit of transporting patients to a facility offering multidisciplinary treatment, even if vital signs stabilize to the point.